2019
DOI: 10.1002/vms3.147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the extent of neoplastic infiltration in small intestinal tumours in dogs

Abstract: There is currently a lack of evidence‐based guidance when determining surgical margins for small intestinal tumours in dogs. The purpose of this study is to help the surgeon make informed clinical decisions about margins when confronted with a small intestinal mass. Twenty‐seven canine small intestinal tumours were histologically diagnosed and then had further histological assessment at every centimeter from the edge of the palpable tumour to the surgical margin in oral, aboral and mesenteric directions. In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Unfortunately, intestinal lymphomas have the tendency to infiltrate well beyond the palpable mass, and the complete resection is less feasible than for other intestinal tumour types. 12 The US characteristics of peritoneal lymphomatosis have been previously described in cats, and most common findings included thickened, hypoechoic plaques or sheets of abnormal tissue throughout the mesentery, together with peritoneal effusion. 6 7 In this case, peritoneal effusion was absent, while commonly described both in humans and feline patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unfortunately, intestinal lymphomas have the tendency to infiltrate well beyond the palpable mass, and the complete resection is less feasible than for other intestinal tumour types. 12 The US characteristics of peritoneal lymphomatosis have been previously described in cats, and most common findings included thickened, hypoechoic plaques or sheets of abnormal tissue throughout the mesentery, together with peritoneal effusion. 6 7 In this case, peritoneal effusion was absent, while commonly described both in humans and feline patients.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the fact that the margins of the excised jejunal mass were infiltrated as well could have brought to a peritoneal dissemination, visible at US examination only after some months. Unfortunately, intestinal lymphomas have the tendency to infiltrate well beyond the palpable mass, and the complete resection is less feasible than for other intestinal tumour types 12…”
Section: Discussionmentioning
confidence: 99%
“…A recent report that evaluated the margins in tumours that arose in the small intestine found that a 3 cm margin on the rostral side, anal side and mesenteric side for adenocarcinoma, and a 2 cm margin at each of these sites for sarcoma were 100% clean, although a 0-1 cm margin was a clean margin for GIST in two dogs. 18 With the current procedure, it is almost impossible to take a 2-3 cm margin on the mesenteric side if the major and minor duodenal papillae are to be preserved. In our case, the tumour was removed with clean margins, which suggests that this procedure can be applied to GIST that occurs in the proximal duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that indices of Ki67 and MGMT might specifically reflect surgical and chemotherapeutic outcomes, respectively, and these may serve as determinants to select a first‐line treatment. More importantly, surgical treatment is often restricted to SIL in dogs, and a therapeutic strategy should be preferentially determined by classification of clinical staging, absence or presence of perforation, obstruction, or peritonitis, and the need for a surgical biopsy for diagnosis 1,6 . Therefore, we should note that these selection criteria could be applied to dogs with localized SIL without systemic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The human literature recommends the combination of surgery with chemotherapy for SIL 2‐5 . However, there is a paucity of information in the veterinary literature regarding the combination of surgery with chemotherapy 1,6 . One report showed that there was no difference in the MSTs for dogs that did and did not undergo surgery 1 .…”
Section: Introductionmentioning
confidence: 99%